2004
DOI: 10.1007/s00125-004-1334-6
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemia and mortality from all causes and from cardiovascular disease in five populations of Asian origin

Abstract: For prediction of premature death, 2-h PG was superior to FPG in several Asian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
195
3
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(212 citation statements)
references
References 52 publications
12
195
3
2
Order By: Relevance
“…In the DECODA study, more than half the patients with diabetes had isolated postprandial hyperglycaemia [70], which is additionally a powerful predictor of cardiovascular disease and premature death [71]. DPP-4 inhibitors are known to reduce both FPG and PPG [72].…”
Section: Discussionmentioning
confidence: 99%
“…In the DECODA study, more than half the patients with diabetes had isolated postprandial hyperglycaemia [70], which is additionally a powerful predictor of cardiovascular disease and premature death [71]. DPP-4 inhibitors are known to reduce both FPG and PPG [72].…”
Section: Discussionmentioning
confidence: 99%
“…The DECODE study examined 22 adult European cohorts for diabetes, and Ͼ27,000 people were followed up for mortality for an average of 11 years (17). The DECODA study followed five cohorts of Japanese and Indian origin (18). We used the RR of deaths in 3,482 Asian Indians living in Mauritius and Fiji to recalculate the number of deaths for Southeast Asia and compared it with the number of deaths derived using published RRs of dying from studies conducted in Europe and the U.S.…”
Section: Validationmentioning
confidence: 99%
“…The subjects of the I/C group consumed at breakfast a 250 ml can (250 kcal) of PBF (Inslow, previously designated as MHN-01; the composition are reported previously (Arai et al 2004), as shown in Table 1; Meiji Dairies Corporation, Odawara) together with foods that were 250 kcal less than their usual breakfast to hyperglycemia has also been considered a risk factor for cardiovascular complications (Tominaga et al 1999;Temelkova-Kurktscheive et al 2000;Risso et al 2001;Chiasson et al 2002;Hanefeld et al 2004;Nakagami et al 2004). Many experimental and epidemiological studies have shown that increased postprandial plasma glucose (PG) levels may have equally or even more harmful effects than fasting hyperglycemia (Tominaga et al 1999;Temelkova-Kurktscheive et al 2000;Risso et al 2001;Nakagami et al 2004), and the reduction of postprandial plasma glucose levels delays the development of cardiovascular complications (Chiasson et al 2002;Hanefeld et al 2004). Postprandial hyperglycemia is a recognized consequence of the effects of both insulin resistance and the impairment of early insulin secretion in response to an oral glucose load (Reaven and Miller 1968;Bruce et al 1988;Lillioja et al 1988).…”
Section: Study Protocol and Traits Examinedmentioning
confidence: 99%